Vocational education and training and the role of comparative international data - Kis, Victoria [Verfasser] (My University, 2022)
“Vocational education and training is often seen as a key means of smoothing school-to-work transition and meeting skills needs in the labour market. The extent to which vocational programmes are used and at what level of education and age they are mostly pursued varies greatly across countries. There are important policy questions regarding the mix of general vs. vocational education that is needed by economies and societies, and what makes a national vocational education and training (VET) system strong. Comparative data and indicators provide the evidence base needed to shed light on these questions. This chapter focuses on comparative data and indicators on three topics: the broad features of national VET systems, the use of work-based learning, and outcomes from VET. For each issue in focus, it sets out what we know thanks to currently available data and highlights key gaps in comparative data. The conclusion identifies three issues, on which the gaps could be filled with modest investment of data collection resources, and would yield large benefits in terms of comparative analysis. These are collecting data on the balance of general vs. vocational content of programmes, agreeing a definition for apprenticeships and developing definitions for programme orientation at tertiary levels.” (author’s abstract; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; I 1 Internationale Berufsbildung; 370; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Internationaler Vergleich; Indikatoren; Bildungsberichterstattung; Datenanalyse; OECD